Students' Uses And Gratification Expectancy For E-Learning Resources - Makingu, Howard Mondi (2007)
The purpose of this researchis to analyse 'how and why' these Uses and Gratification Expectancy (UGE) aspects of students "communication behaviour' towards e-learning resources influence their learning experience, in a blended learning strategy.